A Review on EMI Issues in High speed Designs and Solutions - Uma Maheswari Y; Amudha A; Ashok Kumar L (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2022)
As data speed on printed circuit boards have increased, new difficulties have evolved and necessitating the development of new analytical methodologies and solutions. It will be necessary to continue research in order to keep up with the ever-increasing data rates and smaller form factors. The literature and issue pertaining to the EMI/EMC of printed circuit boards are reviewed in detail in this paper for the purpose of providing an overview and to assist people looking for more extensive references related to this area. This review includes EMI issues related to high speed PCB, EMI measurement techniques using software and hardware and solution for the EMI issues. Also reviewed the use of electromagnetic band gap (EBG) technology to minimize electromagnetic interference (EMI). In recent years, there have been a number of articles describing the several uses of EBG for the purpose of blocking undesired radiation at discontinuities. Various EBG structure performances with its applications are analysed and detailed.